Transformasi Digital dalam Keuangan Islam: Peluang dan Tantangan - Sudarmanto, Eko; Yuliana, Indah; Wahyuni, Nanik; Yusuf, Sitti Rabiah; Zaki, Ahmad (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to explore the impact of digital transformation in the Islamic finance sector, discussing the opportunities and challenges that arise with the adoption of digital technologies. The study utilizes a qualitative method with literature review approach. Digital transformation includes the implementation of innovations such as financial technology (fintech), blockchain, and artificial intelligence within the context of Sharia-compliant finance. The results of the discussion present a comprehensive overview of how digitization affects Islamic financial products and services, considering the potential for increased operational efficiency, financial inclusivity, and more effective adherence to Islamic financial principles. Meanwhile, challenges such as data security, regulations, and market acceptance are also outlined, emphasizing the efforts required to optimize the benefits of digital transformation in the realm of Islamic finance.